Prediksi Harga Bekatul menggunakan Metode Fuzzy Time Series - Oky Krisdiantoro; Budi Darma Setiawan; Muhammad Tanzil Furqon (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Rice bran is one of the raw materials used as a mixture of animal feed concentrates, the use of rice bran in animal feed concentrates is 10% -30% from about 10 other types of raw materials mixed. with the number of percentages used, the company needs to pay attention to the availability of rice bran and also the price that changes every month, if the price of rice bran is too expensive it will change the basic price of animal feed concentrate, so the company must be able to predict the price of rice bran in the next month so that they can supply more rice bran when the prices would increase. To predict prices, we can use the fuzzy time series method with reference to historical data from the previous months, with which we can find out the price predictions of rice bran in the following month. The results of this study are expected to be able to help animal feed concentrate companies to be able to predict the price of bran in the coming months, in this study the best predictions resulted in a MAPE value of 4.43% with a number of training data 36 and interval length 12.